2013
DOI: 10.1111/cch.12036
|View full text |Cite
|
Sign up to set email alerts
|

Paediatricians' decision making about prescribing stimulant medications for children with attention‐deficit/hyperactivity disorder

Abstract: Paediatricians' decisions to prescribe stimulant medications are influenced by multiple factors that operate concurrently and interdependently. Paediatricians do not make decisions about prescribing in isolation; rather, they actively involve parents, teachers and patients, to arrive at a collective, well-informed decision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The censusADHD study was established to recruit a nationwide cohort of Australian children aged 6–11 years living with ADHD. As expected from previous reports (Chow et al, 2014), almost two-thirds of the index children were first diagnosed with ADHD by paediatricians. Consistent with other population-based studies (Bianchini et al, 2013; Rowland et al, 2015), the proportion of index children of each ADHD subtype was as expected, indicating that the sample is representative of the DSM-IV diagnostic criteria for ADHD cases in the population.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The censusADHD study was established to recruit a nationwide cohort of Australian children aged 6–11 years living with ADHD. As expected from previous reports (Chow et al, 2014), almost two-thirds of the index children were first diagnosed with ADHD by paediatricians. Consistent with other population-based studies (Bianchini et al, 2013; Rowland et al, 2015), the proportion of index children of each ADHD subtype was as expected, indicating that the sample is representative of the DSM-IV diagnostic criteria for ADHD cases in the population.…”
Section: Discussionsupporting
confidence: 87%
“…In Australia, the treatment and management of ADHD are predominantly undertaken by paediatricians (Chow et al, 2014); approximately 92% of patients with ADHD receive treatment under the care of a paediatrician rather than a psychiatrist or general practitioner (Preen et al, 2008). Current international guidelines recommend multimodal approaches that include pharmacological and psychosocial interventions for the management of ADHD (Coghill et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…An interview-based study done in Australia in 2014 to evaluate paediatricians' decision making about stimulant prescribing showed it to be a complex process. 18 They found that there are clinical, child/family and paediatrician factors, all of which are weighed up before a decision is made. In the paediatrician factors, previous experience and success with the medication were important.…”
Section: Discussionmentioning
confidence: 99%